Computer security and encryption : an introduction - Chauhan, S. R.; Jangra, S. (Mercury Learning and Information, 2020)
Designed to meet the needs of beginners as well as more advanced readers, this book describes various aspects of cryptography and system security, with a particular emphasis on the use of rigorous security models and practices in the design of networks and systems. -- Edited summary from book.
Includes index.
Keywords: Computer networks -- Security measures.; Computer security.; elektronické knihy; electronic books